Sex-specific association between urinary kisspeptin and pubertal development - Rafaella Sales de Freitas; Thiago F A França; Sabine Pompeia (Endocrine Connections, 2022)
Kisspeptins play a crucial role during pubertal development, but little is known about how their peripheral concentrations relate to sexual maturation. This is partly due to the lack of non-invasive, quick, and reliable peripheral kisspeptin measures, which limit widespread testing. Here, we investigated the relationship between kisspeptin concentrations measured from midstream urine samples with 2-h retention periods and developmental markers (age, self-reported pubertal status, and saliva concentrations of testosterone and DHEA sulphate ) in 209 typically developing 9- to 15-year-old males and females. As a result of the study, we found marked sex differences. Kisspeptin concentrations were similar between sexes until around 12 years of age, but, thereafter, kisspeptin concentrations in females did not change significantly, whereas, in males, there was a clear positive correlation with developmental measures. Our results replicate previous findings regarding kisspeptin concentration changes across the pubertal transition obtained from blood samples, suggesting that measuring these peptides in urine has the potential for exploring kisspeptins’ peripheral effects and their associations with pubertal status.